Bruceae Fructus Oil Inhibits Triple-Negative Breast Cancer by Restraining Autophagy: Dependence on the Gut Microbiota-Mediated Amino Acid Regulation - Su, Jiyan; Chen, Xiaohong; Xiao, Yuanjie; Li, Dan; Li, Muxia; Li, Hongfu; Huang, Jiangjian; Lai, Zhengquan; Su, Ziren; Xie, Yizhen; Zhu, Dajiang; Chen, Qianjun; et al. (Frontiers in Pharmacology, 2021)
Triple-negative breast cancer (TNBC) has been acknowledged as an aggressive disease with worst prognosis, which requires endeavor to develop novel therapeutic agents. Bruceae fructus oil (BO), a vegetable oil derived from the fruit of Brucea javanica (L.) Merr., is an approved marketable drug for the treatment of cancers in China for several decades. Despite that the anti-breast cancer activity of several quassinoids derived from B. javanica have been found, it was the first time that the potential of BO against TNBC was revealed. Although BO had no cytotoxicity on TNBC cell lines in vitro, oral administration of BO exhibited a gut microbiota-dependent tumor suppression without toxicity on the non-targeted organs in vivo. By metagenomics and untargeted metabolomics, it was found that BO not only altered the composition and amino acid metabolism function of gut microbiota, but also regulated host’s amino acid profile, which was in accordant with the metabolism alternation in gut microbiota. Moreover, activity of mTOR in tumor was promoted by BO treatment as indicated by the phosphorylation of 4E-binding protein 1 (4E-BP1) and ribosomal protein S6, and hyper autophagy was consequently restrained. By contrast, the failure of tumor suppression by BO under pseudo germ-free (PGF) condition came with indistinctive changes in autophagy and mTOR activity, implying the critical role of gut microbiota in BO’s anti-cancer activity. The present study highlighted a promising application of BO against breast cancer with novel efficacy and safety.